Exploring Islamic Social Environment's Role in English Proficiency: ‘‘Mondok’’ vs ‘‘Nyolok’’ Students - Sitti Surya Pramudita; Indah Werdiningsih; Anita Fatimatul Laeli (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines English proficiency differences between Mondok (full-time Islamic boarding) and Nyolok (daily commuting) students in an Islamic vocational Pesantren in Jember, Indonesia. Using mixed-methods with 40 female students (20 each group), tests revealed Mondok students scored significantly higher (68.50 vs. 63.25; p = .038). Despite this 5.25-point difference, both groups achieved intermediate proficiency through distinct pathways—demonstrating Complex Dynamic Systems Theory's principle of equifinality. Qualitative data showed Mondok students, despite technological constraints, developed adaptive strategies like peer learning and utilized limited "kiriman" time effectively. In contrast, Nyolok students with technological access struggled with consistency and speaking anxiety due to less structured environments. The findings illustrate how different environmental conditions within the same institution trigger unique adaptive patterns, highlighting CDST's value in explaining non-linear language development in Islamic educational contexts and offering practical implications for differentiated instruction in vocational Pesantren.